2019
DOI: 10.1002/smll.201903422
|View full text |Cite
|
Sign up to set email alerts
|

Exceedingly Small Gadolinium Oxide Nanoparticles with Remarkable Relaxivities for Magnetic Resonance Imaging of Tumors

Abstract: Gd chelates have occupied most of the market of magnetic resonance imaging (MRI) contrast agents for decades. However, there have been some problems (nephrotoxicity, non‐specificity, and low r1) that limit their applications. Herein, a wet‐chemical method is proposed for facile synthesis of poly(acrylic acid) (PAA) stabilized exceedingly small gadolinium oxide nanoparticles (ES‐GON‐PAA) with an excellent water dispersibility and a size smaller than 2.0 nm, which is a powerful T1‐weighted MRI contrast agent for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…Gadolinium oxide [4,5], gadolinium fluoride [6,7] and gadolinium phosphate [8] NPs have been synthesised and tried as T 1 contrast agents. Most recent examples are focused on targeted T 1 Gd 2 O 3 NPs [9], dual T 1 -T 2 MRI probes [10], hybrid MRI/fluorescent probes [11,12] and theranostic (theraphy + diagnostic) probes [13] for tumour imaging. A Gd 2 O 3 -NP hybrid CT/MRI probe functionalised with bisphosphonate was used by Mastrogiacomo et al to visualise calcium phosphate bone cement [14].…”
Section: Paramagnetic Gd 2 O 3 Nanoparticlesmentioning
confidence: 99%
“…Gadolinium oxide [4,5], gadolinium fluoride [6,7] and gadolinium phosphate [8] NPs have been synthesised and tried as T 1 contrast agents. Most recent examples are focused on targeted T 1 Gd 2 O 3 NPs [9], dual T 1 -T 2 MRI probes [10], hybrid MRI/fluorescent probes [11,12] and theranostic (theraphy + diagnostic) probes [13] for tumour imaging. A Gd 2 O 3 -NP hybrid CT/MRI probe functionalised with bisphosphonate was used by Mastrogiacomo et al to visualise calcium phosphate bone cement [14].…”
Section: Paramagnetic Gd 2 O 3 Nanoparticlesmentioning
confidence: 99%
“…It could also be expected that the as-prepared NPs possess the potential to be applied as MRI imaging contrast agent due to the addition of Gd [32,33]. In vitro experiment demonstrated that T1 signal intensity was enhanced with the increasing concentration of HMON@ CuS/Gd solutions.…”
Section: Preparation Characterization and In Vitro Photo-thermal Effmentioning
confidence: 97%
“…Dendritic polymers provide a great scaffold for holding paramagnetic ions (i.e., Gd 3+ , Mn 2+ ) (Connah & Angelovski, 2018), encapsulating magnetic oxides (i.e., Fe 3 O 4 , Gd 2 O 3 ) (Esmaeili et al, 2019) or accommodating other MRI probes (i.e., 19 F‐MRI nanoprobes, nitroxide radical units) (Celentano et al, 2020; Pinto et al, 2019). These systems not only significantly improve the blood circulation time and in vivo stability of contrast agents, but also increase their longitudinal relaxation efficacies and concentrations at local tumor sites, thereby enabling sensitive detection of early‐stage cancer and long‐term monitoring of cancer progression (Shen et al, 2019). Dendrimer‐based MR contrast agents for cancer diagnosis has been previously discussed in a few review papers (L. Ding, Lyu, et al, 2018; McMahon & Bulte, 2018).…”
Section: Applications Of Dendritic Nano‐scale Systems In Cancer Diagnmentioning
confidence: 99%